High Manganese Tolerance and Biooxidation Ability of Serratia marcescens Isolated from Manganese Mine Water in Minas Gerais, Brazil - Barboza, Natália R.; Morais, Mônica M. C. A.; Queiroz, Pollyana S.; Amorim, Soraya S.; Guerra-Sá, Renata; Leão, Versiane A. (Frontiers in Microbiology, 2017)
Manganese (Mn), though an indispensable metal for biological function, could result in toxicity at elevated concentrations. Consumption of solar salt contaminated with metals like Mn, could be a major route for human exposure. The mitigation of Mn from such contaminated sites by Mn-tolerant bacteria provides a safe and environment-friendly alternate technology for the future. Therefore, this study was undertaken to isolate and identify Mn resistant bacteria from water samples collected from a Mn mine in the Iron Quadrangle region (Minas Gerais, Brazil). Two bacterial isolates were identified as Serratia marcescens based on morphological, biochemical, 16S rDNA gene sequencing and phylogeny analysis. Maximum resistance of the selected isolates against increasing concentrations of Mn(II), up to 1200 mg L−1 was determined in solid media. A batch assay was developed to analyze and quantify the Mn removal capacities of the isolates. Biological Mn removal capacities of over 55% were detected for both isolates. Whereas that mechanism like biosorption, precipitation and oxidation could be explaining the Mn removal, we seek to give an insight into some of the molecular mechanisms adopted by S. marcescens isolates, using leucoberbelin blue I assay, Mn(II) oxidation by cell-free filtrate and electron microscopy and energy-dispersive X-ray spectroscopy analyses. Overall, these results indicate that S. marcescens promotes Mn removal by the formation of Mn oxides precipitates around the cells, which should be further explored for potential biotechnological applications for water recycling both in hydrometallurgical and mineral processing operations.